2015
DOI: 10.1186/s13023-014-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

New biomarkers for early diagnosis of Lesch-Nyhan disease revealed by metabolic analysis on a large cohort of patients

Abstract: BackgroundLesch-Nyhan disease is a rare X-linked neurodevelopemental metabolic disorder caused by a wide variety of mutations in the HPRT1 gene leading to a deficiency of the purine recycling enzyme hypoxanthine-guanine phosphoribosyltransferase (HGprt). The residual HGprt activity correlates with the various phenotypes of Lesch-Nyhan (LN) patients and in particular with the different degree of neurobehavioral disturbances. The prevalence of this disease is considered to be underestimated due to large heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Strikingly, AICAR is accumulated in body fluids of patients suffering purine metabolism diseases, including hypoxanthine-guanine phosphoribosyltransferase-deficient patients (15,26). It should be stressed that the levels of AICAR accumulated by these patients (15) are way below those resulting in synthetic lethality in yeast cells (this work). However, should AICAR have similar effects in human cells than the ones observed in yeast, it could contribute to the phenotypic outcome of these complex developmental genetic diseases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Strikingly, AICAR is accumulated in body fluids of patients suffering purine metabolism diseases, including hypoxanthine-guanine phosphoribosyltransferase-deficient patients (15,26). It should be stressed that the levels of AICAR accumulated by these patients (15) are way below those resulting in synthetic lethality in yeast cells (this work). However, should AICAR have similar effects in human cells than the ones observed in yeast, it could contribute to the phenotypic outcome of these complex developmental genetic diseases.…”
Section: Discussionmentioning
confidence: 77%
“…However, should AICAR have similar effects in human cells than the ones observed in yeast, it could contribute to the phenotypic outcome of these complex developmental genetic diseases. Accordingly, we recently found that, in addition to AICAR accumulation, NTP levels were significantly lower in erythrocytes from a large cohort of hypoxanthine-guanine phosphoribosyltransferase-deficient patients (15).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However one of the major limitations associated with this classification has been the heterogeneity of HPRT-deficient phenotypes which, along with the varying degrees of severity, can lead to misclassification and diagnostic uncertainty (Ceballos-Picot et al, 2015;Fu, Ceballos-Picot, et al, 2014). Consequently, there have been multiple attempts to develop new biomarkers that will facilitate diagnostic and also allow a more refined classification of the clinical phenotypes of LND (Ceballos-Picot et al, 2015). Circulating miRNAs are currently used as biomarkers not only in cancer but also in neurological diseases.…”
Section: Mirnas Biomarkers For Lndmentioning
confidence: 98%
“…accumulate when its riboside precursor AICAR is provided to the cell, but also in several metabolic diseases. Indeed, ZMP as well as ZDP and ZTP were found at very high concentrations (ZTP reaching even higher levels than ATP) in red blood cells of an AICAR transformylase IMP-cyclohydrolase-deficient patient lacking the enzyme that catalyzes the last two steps of the purine biosynthesis pathway (25) and was the best marker for hypoxanthine-guanine phospho-ribosyl-transferase deficiency in a large cohort of Lesch-Nyhan syndrome patients (26). The precise role of ZMP in the etiology of these diseases is unclear but should be addressed in connection with the fact that treating eukaryotic cells with AICAR at high concentration is toxic.…”
Section: Aicar Monophosphate Toxicitymentioning
confidence: 99%